A Study of Applying Design Patterns to A Role Playing Game - Jung-Hua Lo; Chi-Shain Yeh (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the rapid of the deployment of computer systems, people in the modern society are increasingly dependent on the hardware and software systems.  When the demand for computer systems increases, the possibility of crises from computer failure will also increase.  Therefore,, in order to achieve a desired level of quality, the experienced software team must have a better design method to establish the system.  That is, it is very important to choose a better approach that can be applicable to develop the complex software system. The experienced designers will record the design problems which they felt hard to solve or they took much time to solve. When they meet the similar problems later, they would refer to the record. Design patterns are produced from the record. This Paper aims at explaining how to apply the design patterns in the game framework through a simple example by taking the Role Playing Game as example and adding design patterns; it also tries to make a judgment whether the software quality has been improved by using the object-oriented software quality model to test the software quality of the Role Playing Game without the design patterns and that with the deign patterns. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4664